PENGARUH BOBOT RIMPANG DAN KOMBINASI MEDIA TANAM TERHADAP PERTUMBUHAN BIBIT JAHE MERAH (Zingiber officinale var.rubrum) - Mustiani, Yuni Eka; Tanari, Yulinda; Managanta, Andri Amaliel (Universitas Trilogi, 2022)
Ginger as a biopharmaca commodity plant occupies a very important position in the economy of the Indonesian people so it is important to be cultivated. The study aims to determinate the best rhizome weight and composition of planting media and their interaction with the initial growth of red ginger seedlings. this study was designed using a randomized block factorial design with 2 treatment factor consisting of the first factor being planting media (M) consisting of: M1 : soil; M2: soil + sand + cow manure (1:1:1); M3: soil + sand+chicken manure ( 1:1:1); M4: soil + sand + goat manure (1:1:1); M5:soil + husk charcoal + cow manure (1:1:1); M6: soil+husk charcoal + chicken manure (1:1:1); M7: soil + husk charcoal + goat manure (1:1:1). the second factor is the weight of the rhizome (R) which consists of R1: rhizome weight 10 ≥ to <20 grams; R2 rhizome weight ≥20 to ≤30 grams. The result showed that the treatment of the use of rhizome weight of ≥20 to ≤30 grams significantly affected plant height, the number of leaves, shoot diameter, and several shoots. the use of the composition of the planting media (M5) gives the best effect on the age parameters of sprouting. there was no interaction on all observed parameters.